2022
DOI: 10.3390/ijms232314538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subtoxic Concentrations of Atrazine, Cypermethrin, and Vinclozolin on microRNA-Mediated PI3K/Akt/mTOR Signaling in SH-SY5Y Cells

Abstract: Endocrine-disrupting chemicals (EDCs) are different natural and synthetic chemicals that may interfere with several mechanisms of the endocrine system producing adverse developmental, metabolic, reproductive, and neurological effects in both human beings and wildlife. Among pesticides, numerous chemicals have been identified as EDCs. MicroRNAs (miRNAs) can regulate gene expression, making fine adjustments in mRNA abundance and regulating proteostasis. We hypothesized that exposure to low doses of atrazine, cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…EDCs have been shown to affect the neuronal system in both animals and humans. Using novel bioinformatics analyses, Dr. Hrelia and her team published a study in this Special Issue [ 6 ] and revealed that exposure of a neuroblastoma cell line, SH-SY5Y, to subtoxic concentrations of vinclozolin (VNZ) dysregulated microRNA (miR-29-3p) expression as well as perturbed the expression of its downstream ADAM12 and CDK6, which may, in turn, activate the PI3K/Akt/mTOR signaling pathway and suppress tumor suppressor p53 level. This observation was specific to VNZ as the authors compared the effects with two other EDCs, atrazine and cypermethrin, which are commonly used in the agriculture industry.…”
mentioning
confidence: 99%
“…EDCs have been shown to affect the neuronal system in both animals and humans. Using novel bioinformatics analyses, Dr. Hrelia and her team published a study in this Special Issue [ 6 ] and revealed that exposure of a neuroblastoma cell line, SH-SY5Y, to subtoxic concentrations of vinclozolin (VNZ) dysregulated microRNA (miR-29-3p) expression as well as perturbed the expression of its downstream ADAM12 and CDK6, which may, in turn, activate the PI3K/Akt/mTOR signaling pathway and suppress tumor suppressor p53 level. This observation was specific to VNZ as the authors compared the effects with two other EDCs, atrazine and cypermethrin, which are commonly used in the agriculture industry.…”
mentioning
confidence: 99%